A supramolecular dissociation strategy for protein sensing. Issue 97 (13th October 2015) - Wang, Hui; Zhuang, Jiaming; Raghupathi, Krishna R.; Thayumanavan, S.
Abstract : We report a simple, robust, and general strategy for protein detection based on supramolecular dissociation. Abstract : We report a simple, robust, and general strategy for protein detection based on supramolecular dissociation. The simplicity of the design is exemplified by the fact that the host assemblies can be widely varied and that these assemblies can be achieved from commercially available surfactants. An operating mechanism that is consistent with all the data has been proposed.